Smart home security system - Bahrin, Muhammad Harith; Abdul Rahim, Ruzairi; Tee, Kian Sek; Abdul Manaf, Mohamad Shukri; Wahap, Ahmad Ridhwan; Mohamed Din, Shahrulnizahani; Ahmad, Nasarudin; Mohd Nayan, Norkharziana; Mohd Zain, Rasif; Pusppanathan, Jaysuman (Penerbit UTHM, 2022)
The most common Internet of Things (IoT) component is the smart home, which is described as a home with technology features that ensure the safety and well-being of its inhabitants. A smart home is a networked home with numerous sensors, actuators, and devices that can be managed and accessed remotely through network communication. The latest project that we can see for now is the usage of application by phone and connected to the devices to control what happen at our home and get notify if there is something wrong. However, in the IoT world, an increase in the phenomenon of user privacy data leakage and security vulnerability should not be ignored. Describes a range of important research needs for future IoT systems, including protection and privacy, and depicts the general meanings for the key security aspects within the IoT domain. If the service infrastructure is built without understanding predictable security vulnerabilities, outsiders with malicious intent can cause consumer privacy data leakage, social infrastructure paralysis, and economic losses, as well as a risk to human life in extreme cases. [1]